Pemanfaatan Limbah Nangka (Jerami) sebagai Atraktan Lalat pada Flytrap - Okti Dwi Wulansari; Sarjito Eko Windarso; Narto Narto (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Flies are vector in the spreading of some diseases among humans. The diseases can be transmitted through mechanical transmission, i.e. via the adherent of fly’s body part, such as proboscis, and then spreaded to healthy people by means of contaminated substances (food, drinks,and water). One of the efforts to control flies is using physical-mechanical-physiological technique, e.g. by using flytrap with attractant. One of substances that can be utilized as fly attractant is jackfruit straw waste because of its sweet aroma. This study was aimed to identify themost effective weight of jack-fruit straw waste for catching flies, and to know the number of trapped flies in each weight attractant (5,50 gr; 27,50 gr; and 55,50 gr). This study was an experiment with post test only control group design. The experiment was conducted by placing fourflytraps in a row, consisted of three treatment groups and one group as control, in three replications. The result of this study shows that the average number of trapped flies for 5,50 gr attractant weight variation was 47; for 27,50 gr was 76; for 55,35 gr was 102; and for the control groupwas 12. The statistical result using one way anova at ? = 0,05 obtained p-value < 0,001; whichmeans that the adding of attractant of jackfruit straw waste (straw) significantly affect the number of trapped flies on flytrap. The subsequent LSD test found that the most effective weight attractant was 55,35 gr.